Legal Protection for Children in The School Environment: Between Regulation and Implementation - Bambang Sukamto; Nino Agung Perdana; Ratna Galuh Manika Trisista; Mipasya Ratu Plasmesti (AMCA, 2026)
The phenomenon of violence against students is still a serious problem in Indonesia, even though various regulations regulate child protection. Data from the Ministry of PPPA, Komnas Anak, and KPAI show a significant number of cases, ranging from physical, psychological, to sexual violence. The difference in case numbers between institutions confirms that the problem of child protection is not only in the regulatory aspect, but also in the implementation and reporting mechanisms. This background is what prompted this study to examine the extent to which legal protection regulations for children in schools are implemented in real terms. (1) How are the legal regulations in safeguarding children's rights in schools according to the applicable regulations? (2) How is the legal protection implemented in practice? This study aims to analyse child protection regulations in educational units and examine their implementation and challenges. The research method uses a normative juridical approach supported by empirical data. Primary data was obtained through interviews with school principals, teachers, and parents, while secondary data came from laws and regulations, legal documents, and academic literature. The method used is qualitative descriptive analysis. Research data shows that the legal protection regulations for children in schools have been quite strong, including the 1945 Constitution, Law No. 35 of 2014, Law No. 20 of 2003, Permendikbud No. 82 of 2015, and the Convention on the Rights of the Child. However, its implementation still faces serious obstacles: the non-optimal functioning of the Violence Prevention and Handling Team (TPPK), the lack of socialisation of children's rights, a culture of violence that is still considered part of discipline, and the tendency to resolve cases in a familial manner that ignores the justice of the victim. In conclusion, there is a wide gap between the regulation and implementation of child protection in schools. It is necessary to strengthen child-friendly reporting mechanisms, increase legal awareness among educators, and ensure consistent law enforcement so that children truly feel legal protection.